(untitled) (Journal of the College of Basic Education, 2025)
Carnivalesque and Menippian satire are important elements that Mikhail Bakhtin emphasized in his study of the contemporary novel. Because they reflect the realistic social impact in constructing the narrative event, as carnival is based on distorting social values ​​and overturning their connotations, and is manifested in ritual manifestations and the composition of comical expressions. While the Menippian satire, which is active in situations filled with the carnival spirit, seeks to laugh, and to be freed from the restrictions related to historical situations related to memories and wild imagination, and to highlight the spirit of adventure, and in which scandalous, abnormal, and madness scenes are evident. Imaginary events that take place in the sky or underground, and arguments in thieves’ dens and prisons, in addition to the desecration of the holy things and the sanctification of the profane. The research seeks to identify the satirical and carnivalesque Characteristics that intervene in the construction of the events of the novel, and to highlight the important impact behind the use of these Characteristics. Satire, Menippean satire, Carnivalesque